2022
DOI: 10.51329/mehdioptometry160
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinogram changes before and after silicone oil removal in eyes with macula-off rhegmatogenous retinal detachment

Abstract: Background: Pars plana vitrectomy (PPV) with silicone oil (SO) injection for rhegmatogenous retinal detachment (RRD) repair may adversely affect electroretinographic responses. This study was aimed at assessing retinal function using electrodiagnostic testing after successful PPV with SO tamponade in the eyes with macula-off RRD. Methods: In this interventional comparative study, eligible participants were recruited prospectively over 1 year. We included the eyes that underwent a single successful three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Doslak (1988) stated the electroretinogram (ERG) declined rapidly in silicone oil-filled eyes, the ERG (with a functional retina) was severely reduced to 15% of normal, and even with the most extreme variations of the other parameters, there was still a reduction (60%) of the ERG [ 50 ]. Christou et al (2022) reported that the amplitudes of the a- and b-waves were significantly higher after SO removal than those before SO removal, which means the photoreceptors should have recovered after the silicone oil was removed [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Doslak (1988) stated the electroretinogram (ERG) declined rapidly in silicone oil-filled eyes, the ERG (with a functional retina) was severely reduced to 15% of normal, and even with the most extreme variations of the other parameters, there was still a reduction (60%) of the ERG [ 50 ]. Christou et al (2022) reported that the amplitudes of the a- and b-waves were significantly higher after SO removal than those before SO removal, which means the photoreceptors should have recovered after the silicone oil was removed [ 51 ].…”
Section: Discussionmentioning
confidence: 99%